Accumulation of Heavy Metal Cd and Fe in Rhizophora apiculata Stand Around Lembar Port West Lombok Regency - Valentino, Niechi; Ridzky Prasetyo, Andrie; Anwar Hadi, Muhammad (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The mangrove ecosystem in the Labuan Tereng area needs to be protected and preserved. Mangrove ecosystems have an important role as carbon absorbers and play a role in environmental detoxification through their ability to absorb heavy metals in their surroundings. This study seeks to analyze the ability of Rhizophora apiculata to absorb and retain cadmium (Cd) and iron (Fe) concentrations in the Labuan Tereng mangrove habitat. A systematic sampling approach with a random start was applied, involving 24 plots distributed over three designated stations. Roots and leaves were sampled at each station. Heavy metal concentration analysis for Cd and Fe was conducted at the BSIP Laboratory for Agricultural Instrument Standardization. The study results reveal that root tissues contained the highest concentration levels, namely 615,23 ppm (Fe) and 0,98 ppm (Cd). Therefore, in leaf organs as large as 35,85 ppm (Fe) and 1,09 ppm (Cd). The concentration of heavy metals in R. apiculata has surpassed the permissible limits set by environmental quality standards. Result T-test shows that no significance between Fe and Cd metal in a distance of 0-100 and 100-200 m from the coastline. The translocation factor value of Rhizophora apiculata has phytoextraction properties with a TF value>2 for Cd metal, while for Fe metal, it has phytostabilization properties with a TF value<1. The influence of density on the level of trees and saplings does not have a significant relationship with Cd and Fe metals, where the t-count is > 0.05 and the effect is very weak on Cd and Fe metals.